Square sun, square moon : a collection of sweet sour essays - Reps, Paul, 1895-1990 (Tuttle Pub., 1967)
Some of these writings have appeared in American Fabrics magazine, New York, USA and in Mainichi Daily News, Tokyo, Japan, to whom thanks, thanks. All of them are about human experiences in China, Samoa, Tahiti, Fiji, . Japan, Norway, Sweden and in the author. Their viewpoint is personal, even intimate. So as far as I know they intend to extend your life.